2003
DOI: 10.1111/j.1937-5956.2003.tb00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Amplification in Service Supply Chains: An Exploratory Case Study From the Telecom Industry

Abstract: Evidence on the impact of amplification effects on supply chain performance primarily has been derived from studies in manufacturing industries. In this article we reported on a case study from the telecommunication industry and aimed to analyze relevant root causes and associated countermeasures of the amplification phenomenon in service supply chains. Our case findings confirm the occurrence of upstream amplification of workload in the service supply chain, workload being a more appropriate measure for ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
1
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(116 citation statements)
references
References 22 publications
4
105
1
6
Order By: Relevance
“…Through proposition 6, we showed that the effectiveness and efficiency of technology-enabled information exchanges increases whenever a service supply chain maintains interpersonal relationships between its actors. As such, our findings do not support the argument that ICTs themselves are central coordination mechanisms (Akkermans & Vos, 2003;Arshinder &Deshmukh, 2008). However, Mithas, Ramasubbu, andSambamurthy (2011) argue that a firm's customer management capabilities mediate the impact of information management on firm performance.…”
Section: ------------------------------------------Insert Figure 2 Apcontrasting
confidence: 96%
See 3 more Smart Citations
“…Through proposition 6, we showed that the effectiveness and efficiency of technology-enabled information exchanges increases whenever a service supply chain maintains interpersonal relationships between its actors. As such, our findings do not support the argument that ICTs themselves are central coordination mechanisms (Akkermans & Vos, 2003;Arshinder &Deshmukh, 2008). However, Mithas, Ramasubbu, andSambamurthy (2011) argue that a firm's customer management capabilities mediate the impact of information management on firm performance.…”
Section: ------------------------------------------Insert Figure 2 Apcontrasting
confidence: 96%
“…By exploring the role and input of service customers and service providers, we address methodological shortcomings in service research more broadly (Heinonen et al, 2010), and address specific research priorities in service supply chain research (Maull et al, 2012). As such, this study extends firm-centric studies that typically attempt to transfer insights from traditional supply chain studies into service research by assuming the existence of a mature service supply chain (Frohlich & Westbrook, 2002;Akkermans & Vos, 2003;Ellram et al, 2004), and also contributes to the service sourcing literature (e.g., Allen & Chandrashekar, 2000;Baltacioglu et al, 2007;McIvor, 2010).…”
Section: Theoretical Implicationsmentioning
confidence: 80%
See 2 more Smart Citations
“…Ackerman and Voss (2003) provide an excellent example of a Telco implementing a new customer service process that includes four separate activities, selling, installing, provisioning an billing each of which is carried out by a different department. The interactions between the departments led to enormous amplification where a 10% increase in sales order volumes leads to a 250% increase in provisioning, 140% in installing and 175% in billing (Akkermans and Vos 2003).…”
Section: Reductionismmentioning
confidence: 99%